Folículos residuais subsequentes à aspiração folicular em bovinos - Dórea, Marcus Dantas (2012)
The objective of this study is to evaluate the follicular persistence rate of ovarian follicles of 8 and 12 mm in diameter post-aspiration, through the evaluation of endocrine factors, analyzing the interference of these structures in the normal development of the dynamic growth. Holstein cows (N=13) non-lactating and with two consecutive normal estrous cycles were selected; they were treated with 500 mg of sodium cloprostenol (Sincrocio®) and 3 mg of norgestomet (Crestar®) (D0), 2 mg of estradiol benzoate (Sincrodiol®) (D1), randomly assigned to two treatments characterized by the absence or the presence of norgestomet implants, which were subdivided into four groups: presence of the implant and follicle of 8 mm (G1), absence of the implant and follicle of 8 mm (G2), presence of the implant and follicle of 12 mm (G3) and absence of the implant and follicle of 12 mm (G4). Ultrasound monitoring (Esaote Pie Medical®) was performed twice daily with an interval of 12 hours. The ovarian follicles were aspirated with 12 and 8 mm and evaluated for its persistence to the process of aspiration, when persistent these were aspirated again. The data on dynamics of follicle growth, hormone profile of the blood plasma and follicular fluid were checked for normal distribution, by Shapiro-Wilk test, and compared in different treatments by the student's t test. The steroidogenic profile data of the follicles aspirated at different diameters were analyzed by SAS GLM procedure for the main effect of treatment and the comparisons were made by the F test. The significance level adopted was 5%. Treatment with progesterone did not affect follicular growth. The persistence rate was 74.6%. Treatment with progesterone did not affect (P>0.05) the percentage of residual follicles, independent of the diameter of the follicle, however, the effect of the follicular diameter approached the statistical significance (P=0.07). The residual follicles grow approximately 5 mm per day. Of the residual follicles approximately 65% became active follicles, 12% luteinized follicles and 23% inactive follicles. It was concluded that the follicular persistence occurs in the majority of the follicles more frequently aspirated with 12 mm and most of the residual follicles were active and with high estradiol concentration.